2023
DOI: 10.1038/s41598-023-39046-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cancer-related fatigue based on severity: a systematic review and meta-analysis

Abstract: Cancer-related fatigue (CRF) affects therapeutic compliance and clinical outcomes including recurrence and mortality. This study aimed to comprehensively and comparatively assess the severity-based prevalence of CRF. From two public databases (PubMed and Cochrane Library), we extracted data containing information on both prevalence and severity of fatigue in cancer patients through December 2021. We conducted a meta-analysis to produce point estimates using random effects models. Subgroup analyses were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
7
1
Order By: Relevance
“…In our study women reported more severe fatigue than men (Kang et al, 2023), though there are inconsistent results regarding sex differences (Bensing et al, 1999;Oertelt-Prigione et al, 2021). Biological reasons for these sex differences may be related to reproductive function, psychological framework related to different personality and coping strategies, as well as different social positions for men and women.…”
Section: Discussioncontrasting
confidence: 56%
“…In our study women reported more severe fatigue than men (Kang et al, 2023), though there are inconsistent results regarding sex differences (Bensing et al, 1999;Oertelt-Prigione et al, 2021). Biological reasons for these sex differences may be related to reproductive function, psychological framework related to different personality and coping strategies, as well as different social positions for men and women.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, besides CFS, fatigue is one of the most common morbidities even in the general population, affecting approximately 20% [ 5 ]. Additionally, for certain diseases, fatigue is a critical feature of the representative symptoms with high prevalence, for example, 50% in cancer [ 6 ], 80% in fibromyalgia [ 7 ], and 90% in major depressive disorder (MDD) [ 8 ], respectively. Then, CFS has been identified as the most severe form of medically unexplained fatigue and much more severe than other fatigue-associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, female gender has been linked to CRF in many studies. 9,57,58 However, a large-scale international study could not show any differences in fatigue levels between male and female patients. 59 Besides, a recent study on long-term cancer survivors found fatigue to be more common in men than in women, when adjusted for age, comorbidities, partner, and employment status.…”
Section: Discussionmentioning
confidence: 98%